Acessibilidade na aquisição e implantação de sistemas de governo digital - Cordeiro, Aline Couto Oliveira (2021)
This study aimed to contribute to digital accessibility in government agencies, from the elimination of barriers on the Web, in order to allow people with disabilities to use, browse and interact with websites and applications. The study encompassed 1) accessibility analyses of mobile applications in Brazil, 2) consolidation and synthesis of accessibility practices in models of acquisition and implementation of digital government, and 3) the proposal of a guide for the acquisition of accessible information systems for the Federal University of Lavras. In the first part of the study, an analysis of the specification of accessibility requirements for the development of 24 mobile applications of the Brazilian government was carried out. Later, automatic evaluations were carried out in these applications to verify if they had accessibility barriers. Data collection was performed using freedom of information requests to the agencies to access the apps' requirements specifications. The results showed that only seven of the 24 mobile systems had accessibility requirements included in the acquisition and development, while eight explicitly stated that they did not include such requirements, and others classified it as secret or claimed not to have the information. In the second part of the study, the consolidation and synthesis of accessibility practices in software acquisition models for government agencies were carried out based on national and international models, such as the guide "Good Practices for Digital Accessibility in Development Contracting WEB" of the Brazilian Government; "Normative Instruction No. 1, of April 4, 2019" of the Brazilian Government; the "EN 301 549" (Accessibility requirements for ICT products and services) of the European Union and the "Section 508" of the American Government. With the synthesis of best practices and the study of applications, it was possible to reach the third part of the study, which is preparing a draft resolution proposal for a regulation of the acquisition of information systems for UFLA considering accessibility. As a form of technical contribution, this document will support decision-making by those responsible for purchasing and implementing digital systems at the university.